“I STARTED THE DAY JUST CRYING FOR 2 HOURS STRAIGHT.” ECHO-LOCATING THE VULNERABLE SELF ON INSTAGRAM. - Schreiber, Maria (AoIR Selected Papers of Internet Research, 2021)
Building on previous online-ethnographic fieldwork on the #strokesurvivor-community on Instagram, this contribution dives deeper into practices of echo-locating (Markham 2020) the vulnerable self on Instagram. This paper aims to reconstruct practices of adapting to a new body, identity and self through communicating on Instagram from a symbolic-interactionist perspective. I build on Goffman’s concept of stigma, Charmaz’ studies on adapting to illness and impairment and use the lens of Markham’s (2020) concept of echo-locating the self through online connection, Based on close readings and interpretations of postings, including pictures, captions and comments, as well as interviews with active community members, two critical antipodes of sense- and self-making in the #strokesurvivor-community emerged: First, mourning the loss of the familiar body, self, and identity and related identity goals. Users seek permission to mourn and also validation for their grief through their postings and comments. Second, and probably oppositional, perseverance, or in its extreme form, toxic positivity - this concept refers to a (more or less forced) attitude of optimism while ignoring valid reasons to actually not be positive, a mindset that seems to be embedded in a “contemporary cult of happiness” (Wright 2014) and cruel optimism (Berlant 2010). In the #strokesurvivor-community, a positive mindset and belief in the possibility of regaining physical and mental functions is a recurring theme and strong imperative. The contribution focuses on the reconstruction of patterns and practices of mourning and perseverance and their relevance to the echo-location of the vulnerable self.